Effects of single-node cutting method on the propagation and storage root growth of sweetpotato seedlings - Shi, Kaixuan; Sun, Xuan; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2025)
The efficient propagation of virus-free sweetpotato seedlings is a critical challenge for maintaining stable production. This study evaluated two propagation methods—single-node cutting (SNC) and tuberous root propagation (TRP)—in two cultivars (Beniharuka and Himeayaka). Compared to TRP, SNC significantly improved seedling propagation efficiency, producing over 12 times more transplants in 70 days. SNC seedlings also showed enhanced photosynthetic performance before transplanting. After transplanting to the field, SNC seedlings achieved significantly higher storage root yield (30%-50% increase) without compromising root quality, including starch and sugar content. These findings demonstrate that the SNC method is a highly efficient and practical approach for sweetpotato seedling production. The adoption of this method could contribute significantly to improving the sustainability and productivity of sweetpotato cultivation globally. Keywords: sweetpotato, single-node cutting method, tuberous root propagation method, photosynthesis, transplant quality, yield and quality of storage roots DOI: 10.25165/j.ijabe.20251805.9575 Citation: Shi K X, Sun X, He D X. Effects of single-node cutting method on the propagation and storage root growth of sweetpotato seedlings. Int J Agric & Biol Eng, 2025; 18(5): 59–68.